(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The system of wireless sensor network for an industrial environment monitoring is composed of a number of sensors with a networking capability this can be deployed for real time monitoring purpose. Internet of Things (IoT) system allows object to be sensed remotely across existing network infrastructure. The industrial environment determination involved some parameters such as the Temperature, Gas and Light is measured in the real time by the sensors that send the data to the base station or monitoring room. This paper proposes how such monitoring system can be setup emphasizing on the aspects of low cost and easy maintenance and handling. The benefit of wireless system for monitoring purpose will not only reduce the overall monitoring system cost but will also provide flexibility in term of distance or location. Transfer of sensor data from transmitter section to receiver section through zigbee technology. The project is combined with the advanced ARM programmable technology and the advanced sensor specification. In this system device control is also possible through automatically by giving limit to sensor output.